Using Survey Data to Assess the Distributional Effects of Trade Policy - Porto, Guido G. (World Bank, Washington, DC, 2014)
The author develops and applies a methodology to empirically explore the effects of trade policies on the distribution of income and poverty in developing countries. He uses a methodology based on two links-one connecting trade policies to prices, and another connecting prices to household welfare. The author applies the methodology to the study of the distributional effects of Mercosur on Argentine families. The main finding is that Mercosur benefits the average Argentine household across the entire income distribution. There is evidence of a pro-poor bias of the regional trade agreement: on average, poor households gain more from the reform than middle-income households, whereas the effects on rich families are positive but not statistically significant. Prior to the reform, Argentine trade policy protected the rich over the poor, and after the reform, granted some protection to the poor. As relative pre-Mercosur tariffs are higher on relatively skill-intensive goods, the tariff removals tend to benefit the poor over the rich. These findings indicate that trade reforms may actually help improve the distribution of income and reduce poverty in the country.